Transmembrane protein 88 suppresses hepatocellular carcinoma progression and serves as a novel prognostic factor - Cai, Lin; Du, Yu; Song, Kai; Peng, Peng; Han, Fei (Frontiers in Oncology, 2023)
Background Transmembrane protein 88 (TMEM88) is known to be involved in the canonical Wnt signaling pathway and is implicated in several malignancies. However, the expression, function, and prognostic significance of TMEM88 in hepatocellular carcinoma (HCC) remain unclear. Methods In this study, we analyzed mRNA levels of TMEM88 in HCC specimens from the TCGA dataset (n=374) to explore the correlation between TMEM88 and HCC. We also overexpressed TMEM88 in the Huh7 human HCC cell line to investigate its tumor-related role in HCC. Additionally, we conducted in vivo experiments using a mouse model to further validate the critical function of TMEM88 in modulating HCC growth. Results Our results showed that TMEM88 is negatively correlated with the T stage, TNM stage, and pathological grade of HCC. Higher levels of TMEM88 can help predict better overall survival of HCC in both univariate and multivariate analyses. Similarly, higher TMEM88 is a novel prognostic factor for better disease-specific survival of HCC. Overexpression of TMEM88 in Huh7 cells led to a decreased cell proliferation capacity. Xenograft experiments in a mouse model showed that TMEM88 overexpression can remarkably suppress HCC progression. Conclusions Transmembrane protein 88 suppresses HCC growth both in vitro and in vivo, which can act as a potential prognostic factor with clinical application potential.